2005
DOI: 10.1063/1.1925370
|View full text |Cite
|
Sign up to set email alerts
|

EPR spectra of deuterated methyl radicals trapped in low temperature matrices

Abstract: EPR spectra of CHD 2 , and CD 3 radicals have been investigated in low-temperature matrices of H 2 , D 2 , and Ne at temperatures 1.6-4.2 K. A method of condensation from the gas phase on a cold substrate has been used. With decreasing sample temperature, a transformation of the shape of the CD 3 spectrum in H 2 , D 2 , and Ne matrices and CHD 2 spectrum in H 2 and Ne was observed. This transformation was reversible in the above temperature range. The temperature effects are explained as reflecting a change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Bielski et al reported that the total separation of the four lines of the methyl radical formed after photolysis of nitromethane in a water matrix or a tetrachloride matrix at 77 K was 65 G, in close agreement to our experimental findings of 69.45 G . The EPR parameters of the D3-methyl radical trapped in low-temperature matrices were also reported. It shows a septet of lines with an average hfcc of about 3.59 G. In our experiments we measured an average hfcc of 3.8 G septet lines for the D3-methyl radical (CD 3 ) …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Bielski et al reported that the total separation of the four lines of the methyl radical formed after photolysis of nitromethane in a water matrix or a tetrachloride matrix at 77 K was 65 G, in close agreement to our experimental findings of 69.45 G . The EPR parameters of the D3-methyl radical trapped in low-temperature matrices were also reported. It shows a septet of lines with an average hfcc of about 3.59 G. In our experiments we measured an average hfcc of 3.8 G septet lines for the D3-methyl radical (CD 3 ) …”
Section: Resultssupporting
confidence: 90%
“…Similarly, we predict septet lines for the D3-methyl radical (CD 3 ) due to interaction of the unpaired electron with the three adjacent deuterium atoms 2 H ( I = 1). The methyl radical trapped in low-temperature matrices have been studied by EPR spectroscopy previously; thus, the EPR parameters are already known. It was shown that at 4.2 K, the methyl radical has four EPR lines with a hyperfine coupling constant (hfcc) of an average of about 23.1 G. In agreement with these studies, our experiment at 5 K yields well-resolved and separated quartet lines attributed to the methyl radical with hfcc values of 23.06, 23.12, and 23.27 G (Figure a). Bielski et al reported that the total separation of the four lines of the methyl radical formed after photolysis of nitromethane in a water matrix or a tetrachloride matrix at 77 K was 65 G, in close agreement to our experimental findings of 69.45 G .…”
Section: Resultssupporting
confidence: 83%
“…In the calibration measurements, the microwave cavity was removed from the magnet. It turned out in further experiments that the electron cyclotron resonance line positions was at almost exactly "g" = 28 The Bruker WinEPR software was applied in the simulation. a The principal axes of the A-and g-tensors are assumed to coincide.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…(c) δg ⊥ = −0.018%, while other parameters still correspond to the computed values in vacuum. (d) Experimental spectrum, for CH 3 trapped in solid CO at 4.2 K, Dmitriev and Zhitnikov 28. The Bruker WinEPR software was applied in the simulation.…”
mentioning
confidence: 99%